Ukrainian Antarctic Bibliography: Publications in 2016–2018 - N. G. Videnina; V. P. Rybachuk; A. P. Fedchuk; S. I. Prymachenko; N. S. Petrenko (Ukrainian Antarctic Journal, 2018)
Objectives of the study is to monitor the modern national scientific literature on Antarctic research, first of all, as an element of systematic information and bibliographic as well as scientometric support for the implementation of state scientific and technical programs. Methods: bibliographic search, scientometric analysis, bibliometric analysis, webometric analysis, and expert analysis. Ukrainian scientific journals, collections of scientific works and reference editions, scientific reports on projects for the implementation of the State Special-Purpose Research Program in Antarctica for 2011—2020, as well as national (“Scientific Ukraine”, “Bibliometryka of Ukrainian Science”, “Scientific Periodicals of Ukraine”, etc.) and foreign bibliographic databases (Scopus, Google Scholar, e-Library, and others.) were used as the main information source for compiling the bibliography. Results: The article presents the results of a bibliographic search and scientometric analysis of the scientific works of Ukrainian scholars and professionals, published in domestic and foreign editions, as well as in materials of international bodies of the Antarctic Treaty system in 2016—2018. The bibliographic descriptions of 353 publications, the most of which are articles in periodicals (143 descriptions) as well as conference and symposia proceedings (162 descriptions), are given. The bibliometric analysis of the data obtained reveals a stable strong dynamics of the publication activity of Ukrainian researchers and their significant contribution to the world researches of Antarctica. There is a noticeable increase in the number of publications in domestic and foreign scientific editions that are indexed in the bibliographic database Scopus. According to the portal of Scientific Periodicals of Ukraine of the Vernadsky National Library of Ukraine of the NAS of Ukraine the level of relevance of publications in the Ukrainian Antarctic Journal (2007—2017) is defined. It is revealed that the bibliographic and scientometric articles are included in the top-groups of publications in the journal and have a positive trend of users demand. Conclusions: the list of current bibliography presented in the article complements and continues the bibliography of domestic publications for 2007—2015, which was submitted in previous issues of the Ukrainian Antarctic Journal (in 2009, 2010, 2012, and 2016). The bibliographic descriptions given create a factual basis for the scientometric and expert analysis of development trends and research results of domestic scientists and specialists as well as determination of the contribution of Ukraine to modern Antarctic research. The data obtained indicates the expediency of further implementation of bibliographic support of the State research programs of Ukraine in Antarctica as well as a regular publication of the current and retrospective national Antarctic scientific bibliography.